Characterization of Coupled Flux Qubits by Impedance Measurement Technique; ISEC 2005 - Ploeg S.H.W. van der; Izmalkov A.; Grajcar M.; Il'ichev E.; Linzen S.; Wagner Th.; Hubner U.; Meyer H.-G.; Uchaykin S. V. Sergey Victorovich; Brink A. M. van den; Zagoskin A. M. (2005, 2005)
Title screen